Politik Tubuh Perempuan: Bumi, Kuasa, dan Perlawanan - Susilo, Daniel; Kodir, Abdul (UI Scholars Hub, 2016)
The women’s body in relation with the concept of existence is mutually binding. Body becomes a starting point to look at the existence of women themselves. The women’s as commodity and political instrument historically cannot be separated as the former is in many occasions seen as dangerous, especially if it is uncontrolled. Various policies have been produced by authorities as the expression of control over women’s bodies. Women themselves as the owners of the body are powerless against the control and power over her body. Any resistances to response or demand for more control will simply be labeled as immoral and inappropriate. In fact, state control over the body is actually considered as a result of the willingness of the state’s presence under the pretext of the need for more controlled public good. In other study, Foucault and ecofeminism present stringing struggle of many groups against any form of power over the woman’s body. The formation of power over sexuality is conducted through disciplining the body and through a population policy to regulate the rate of population growth. Foucault criticized the effort to control women’s body. The aim of this article is to prove the power through its apparatus controls women’s bodies through reproductive policies. This paper also describes the mastery correlation of the female body with earth, in relation with the views of ecofeminism. Ecofeminism also takes a more extreme way to be directly involved in saving earth, the first teritory heavily linked with the women’s body. The concern with women’s bodies also means caring about the future survival of human.